Identification of potent natural compounds in targeting Leishmania major CYP51 and GP63 proteins using a high-throughput computationally enhanced screening - Deepak A. Yaraguppi; Sanjay H. Deshpande; Zabin K. Bagewadi; Uday Muddapur; Sushil Anand; Santosh B. Patil (SpringerOpen, 2020)
Abstract Background Leishmaniasis is a disease caused by protozoan forms called Leishmania which infect animals and humans. The drugs have been in use since half a century due to which there have been mutations in the microbe-facilitating drug resistance. So this provides a reason for searching for effective drugs for the disease. In the current work, an effort has been to find such drugs that act on disease-relevant receptors by similarity indexing method, molecular docking, and dynamics studies. The study focused on the rapid expansion of potential anti-leishmanial compounds that could function as novel natural compound structures for future drug Results Similarity indexing of existing drugs with natural compounds using Tanimoto clustering resulted in 4 compounds with similarity index of greater than 0.7 (70% similarity). The molecular docking of the resulted compounds was carried out with therapeutic targets CYP51 and GP63 proteins. N-methyltyrosyl-N-methyltyrosyl-leucyl-alanine from Streptomyces griseus showed higher binding affinity in comparison to inhibitor and other selected natural compounds. Simulation studies revealed that the binding configuration of the compound with targets was highly stable all through 10 ns of simulation time with intact hydrogen bonding. Conclusions The molecular docking and molecular dynamics studies for the selected natural bioactive compound N-methyltyrosyl-N-methyltyrosyl-leucyl-alanine from Streptomyces griseus showed better binding affinity with the selected therapeutics targets and can be further considered for in vitro and in vivo studies which may lead to a possible new drug for the treatment of Leishmaniasis.